STABILISASI LERENG DENGAN APLIKASI SOIL NAILING PADA AREA GALIAN DALAM DAN KEMIRINGAN CURAM - Standyarto, Andrew Nugraha; Prayitno, Andika Yuda; Prayitno, Dedi (Jurnal Jalan Jembatan, 2023)
The aim of study is to determine the effect of applying soil nailing to increase the stability and strengthening of excavation slopes on soil stratification in areas of deep dips and steep slopes. Observations were carried out on New Capital City Toll Road section 3A Karangjoang - KKT Kariangau, a division of the toll road where a structure in the form of a High Voltage Air Line (SUTT) is placed. Deep excavation was carried out at the location, which set the SUTT tower 20 m from the slope of the road route. Tower relocation cannot be carried out, and slope management must be designed to prevent landslides from occurring. Soil condition data was taken from the field at 4 points using boring and SPT methods. Data analysis used the Plaxis 2D Finite Element Analysis (FEA) modelling program and the Mohr-Coulomb soil model to compare two conditions, namely the excavation slope without reinforcement and with soil nailing reinforcement configuration. From the slope stability analysis, excavation design 1 in front of SUTT and design two at the transition have a Safety Factor (SF) > permit in short-term conditions and pseudo-static earthquakes but experience landslides in long-term conditions and coal (lignite) weathering. This study shows that applying soil nailing with a diameter of 10 cm, a length of 12 m and a 12D vertical and 15D horizontal installation configuration meets the SF permitting slope stability according to SNI 8460:2017 on Geotechnical Design Requirements. Key words: slope resistance, soil nailing, deep excavation, high voltage tower, coal weathering (lignite)